2023
DOI: 10.1109/ojemb.2023.3280127
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Jump Height Using Markerless Motion Capture with a Single Smartphone

Abstract: Goal: The countermovement jump (CMJ) is commonly used to measure lower-body explosive power. This study evaluates how accurately markerless motion capture (MMC) with a single smartphone can measure bilateral and unilateral CMJ jump height. Methods: First, three repetitions each of bilateral and unilateral CMJ were performed by sixteen healthy adults (mean age: 30.87 \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Concerning practical applications and accessibility, Aderinola et al [41] showed the viability of using a single smartphone camera for MMC in measuring jump height. This is in line with Washabaugh et al's study [42], which provided a comparative analysis of different pose estimation methods, like OpenPose, Tensorflow MoveNet, and DeepLab-Cut, in walking kinematics.…”
Section: Related Workmentioning
confidence: 99%
“…Concerning practical applications and accessibility, Aderinola et al [41] showed the viability of using a single smartphone camera for MMC in measuring jump height. This is in line with Washabaugh et al's study [42], which provided a comparative analysis of different pose estimation methods, like OpenPose, Tensorflow MoveNet, and DeepLab-Cut, in walking kinematics.…”
Section: Related Workmentioning
confidence: 99%